Relationship Between Duration of Targeted Temperature Management, Ischemic Interval, and Good Functional Outcome From Out-of-Hospital Cardiac Arrest. Issue 3 (March 2020) - Sawyer, Kelly N.; Humbert, Andrew; Leroux, Brian G.; Nichol, Graham; Kudenchuk, Peter J.; Daya, Mohamud R.; Grunau, Brian; Wang, Henry E.; Ornato, Joseph P.; Rittenberger, Jon C.; Aufderheide, Tom P.; Wittwer, Lynn; et al.
Abstract : Objectives: Tailoring hypothermia duration to ischemia duration may improve outcome from out-of-hospital cardiac arrest. We investigated the association between the hypothermia/ischemia ratio and functional outcome in a secondary analysis of data from the Resuscitation Outcomes Consortium Amiodarone, Lidocaine, or Placebo Study trial. Design: Cohort study of out-of-hospital cardiac arrest patients screened for Resuscitation Outcomes Consortium-Amiodarone, Lidocaine, or Placebo Study. Setting: Multicenter study across North America. Patients: Adult, nontraumatic, out-of-hospital cardiac arrest patients screened for Resuscitation Outcomes Consortium-Amiodarone, Lidocaine, or Placebo Study who survived to hospital admission and received targeted temperature management between May 2012 and October 2015. Interventions: Targeted temperature management in comatose survivors of out-of-hospital cardiac arrest. We defined hypothermia/ischemia ratio as total targeted temperature management time (initiation through rewarming) divided by calculated total ischemia time (approximate time of arrest [9-1-1 call or emergency medical services-witnessed] to return of spontaneous circulation). Measurements and Main Results: The primary outcome was hospital survival with good functional status (modified Rankin Score, 0–3) at hospital discharge. We fitted logistic regression models to estimate the association between hypothermia/ischemia ratio and the primary outcome, adjusting for demographics, arrest characteristics, and Resuscitation Outcomes Consortium enrolling site. A total of 3, 429 patients were eligible for inclusion, of whom 36.2% were discharged with good functional outcome. Patients had a mean age of 62.0 years (SD, 15.8), with 69.7% male, and 58.0% receiving lay-rescuer cardiopulmonary resuscitation. Median time to return of spontaneous circulation was 21.1 minutes (interquartile range, 16.1–26.9), and median duration of targeted temperature management was 32.9 hours (interquartile range, 23.7–37.8). A total of 2, 579 had complete data and were included in adjusted regression analyses. After adjustment for patient characteristics and Resuscitation Outcomes Consortium site, a greater hypothermia/ischemia ratio was associated with increased survival with good functional outcome (odds ratio, 2.01; 95% CI, 1.82–2.23). This relationship, however, appears to be primarily driven by time to return of spontaneous circulation in this patient cohort. Conclusions: Although a larger hypothermia/ischemia ratio was associated with good functional outcome after out-of-hospital cardiac arrest in this cohort, this association is primarily driven by duration of time to return of spontaneous circulation. Tailoring duration of targeted temperature management based on duration of time to return of spontaneous circulation or patient characteristics requires prospective study. Abstract : Supplemental Digital Content is available in the text.